Towards More Sustainable Food Systems - Sigrid Kusch-Brandt (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Food systems are under increasing pressure. They must meet the food requirements of a growing world population, and socio-economic changes also influence the type of foods which are under demand. At the same time, food systems are a major contributor to global environmental change, and environmental changes adversely impact agricultural productivity. This Special Issue explores opportunities and challenges towards achieving more sustainable food systems. Essential changes required in food systems are highlighted, such as more effective food distribution, the avoidance or valorisation of food waste, and less meat consumption. How to actually achieve these required changes across food value chains is also presented. This Special Issue supports solution-oriented approaches towards addressing one of most complex challenges of this century. The reader is invited to study the publications included in this Special Issue in detail.
Keywords: 300; consumer attitudes; meat avoiders; meat reducers; environmental concerns; global warming; climate change; sustainability; ecology; planetary health; food security; land; land use consolidation; land-use planning; land tenure; rural development; Rwanda; tenure responsive; tenure responsive land-use planning; tenure security; demographic correlates; food access; household; food insecurity experience scale; Zanzibar; sub-Saharan Africa; vulnerability of food systems; food neophobia; environmental concern; global environmental change; behavior change; willingness to pay (WTP); organic foods; China; Bibliometrics; food rescue; convention center; greenhouse gas emissions; landfill diversion; anaerobic digestion; codigestion; food waste; organic waste; energy and resource recovery; food waste disposal; loss aversion; dead hogs; policy evaluation; hog production; chilli pepper; organic manure; application rate; elevated temperature; rain-shelter plastic house; greenhouse; field; maize; agrobiodiversity; traditional food systems; local knowledge; cultural practices; sustainable agriculture; supply chain coordination; supply chain sustainability; livestock industry; guanxi; trust; dynamic environment; repeated purchase intention; agricultural food system; food policy; food system sustainability; urban agriculture; local development; food governance; stakeholder engagement; food systems; global food regimes; innovation; political–economy; social–ecological systems; transformation; regime shifts; resilience; sustainability in the food sector; food supply chains; food insecurity; food waste and loss; innovation and change